(3GdSdSd GdYPH hGdefgd GdGUdis - (3eMeO Hf CHj HcQ Hf CMeO GdMSjfj GdTdj GdNVQej, HGYdhj, LeGd GdOjf,J (B1093 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ bdhH ChdjGFg HgOi GdJbhi hHYO aEf Gddg HLejd dWag heUGHjM GdYdhe Cf JVef GdJi CMjJ ehGJgG hLeYJ CTJGJgG s
(3BNQgG (B:s
(3hbjd GdMjGA GfbHGV GdbdH JYXje GdQH GfJgi YOO GdeSdejf ef GdCNjGQ GdeWgQ bdhHge GfJgi HMeO Gddg hMSf Yhfg s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B105s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs